2층식 호기성 여상 시스템에서의 하수의 질산화 특성에 관한 연구 - 김덕진; 임도영 (한국수처리학회지, 19(6), 2011)
The aim of this study is to evaluate the performance and nitrification of a two-media BAF system composed of a double-layer bed. The hydraulic load was set at 37.5m^3/m^2·day. The empty bed contact time (EBCT) of the filter bed was 1.3 hour. The backwash was carried out every 48 hours; combined sour air and water backwash(5min), followed by water backwash (10min). The water and air backwash application rate was set at 0.05m^3/min, 0.22m^3/min, respectively. As a result, both BOD and SS removal performance was stable with a removal efficiency of 75% or more regardless of the water quality at more than 15℃. The nitrification reaction started rapidly from the upper part of the filter bed by the point of 60cm at 27℃, at the point of 90cm in case of 13℃. The nitrification reaction was affected by not only the water temperature but also the influence of the removal situation of BOD and SS in the upper part of the filter bed. Additionally, it is possible to quantitatively predict the nitrification rate with an empirical equation with the coefficient water temperature and SS load. The aim of this study is to evaluate the performance and nitrification of a two-media BAF system composed of a double-layer bed. The hydraulic load was set at 37.5m^3/m^2·day. The empty bed contact time (EBCT) of the filter bed was 1.3 hour. The backwash was carried out every 48 hours; combined sour air and water backwash(5min), followed by water backwash (10min). The water and air backwash application rate was set at 0.05m^3/min, 0.22m^3/min, respectively. As a result, both BOD and SS removal performance was stable with a removal efficiency of 75% or more regardless of the water quality at more than 15℃. The nitrification reaction started rapidly from the upper part of the filter bed by the point of 60cm at 27℃, at the point of 90cm in case of 13℃. The nitrification reaction was affected by not only the water temperature but also the influence of the removal situation of BOD and SS in the upper part of the filter bed. Additionally, it is possible to quantitatively predict the nitrification rate with an empirical equation with the coefficient water temperature and SS load. KCI Citation Count: 0